IMPROVED ANTENNA CALCULATION TECHNIQUE IN THE FORM OF OPEN END OF THE ROUND WAVEGUIDE - Karashchuk, N. N.; Rykhalskyi, R. A.; Zaiets, Yu. A.; Sabadash, S. S. (Radio Electronics, Computer Science, Control, 2020)
Context. Directional (slightly directed) antennas of a centimeter wave range of one type or another can be used as separate radiants and be part of antenna arrays. The need to minimize signal power losses in such antennas is a very important and relevant scientific and practical task in any case. Therefore, to minimize signal power losses in antennas of the centimeter wave range, new (improve existing) approaches to reducing these losses should be developed. Objective. The goal of the study is to improve the calculation method of the antenna in the form of an open end of a circular waveguide, which is fed by a coaxial line with a cylindrical dielectric matching transformer, due to the consideration of the end capacitance of this transformer by the equivalent circuit method. Method. To achieve the research objective, the aperture method was used, based on the Huygens-Kirchhoff principle, the method of equivalent schemes, the methods of numerical verification, and natural experiment were applied. Results. New calculation formulas are improved and derived, taking into account the influence of end capacities, which show the following features: the length of a cylindrical dielectric matching transformer should be less than a quarter of the wavelength, therefore the reduction value is determined by the end capacitance; end tanks increase the necessary wave impedance of this transformer; antenna bandwidth increases with decreasing resistance drop, which must be negotiated. The practical value of the research results is to reduce the signal power loss in the antenna due to improved matching, which is determined by the change in the coefficient of standing waves by voltage in a given frequency band of a circular waveguide. For the open end of a circular waveguide with a cylindrical dielectric matching transformer, calculated according to an improved methodology, the radiation patterns both in the E plane and in the H plane approach the radiation patterns of a circular waveguide with in-phase opening. Conclusions. The proposed method was verified by comparing theoretical calculations and experimental studies of the variation of the standing wave coefficient with respect to voltage in the frequency band and radiation pattern in the E and H planes using the well-known and improved methods.